THE INTEGRATION OF HADITH TEACHINGS IN JAVANESE LITERATURE: A STUDY ON SYIIR SEKAR KEDATON BY AL HAJAWI - Waluyo, Hendri; Khairunnisa, Ashma; Waluyo, Teguh (Qawwam : The Leader's Writing, 2025)
This study explores the integration of hadith values within the classical Javanese literary work Syiir Sekar Kedaton by Al Hajawi, highlighting its function as a medium for moral education, character development, and Islamic spiritual guidance. Using a qualitative descriptive-analytical method, the research analyzes the textual content of Sekar Kedaton to identify embedded ethical teachings derived from hadith literature. Primary data consisted of the syiir text itself, while secondary data were drawn from hadith collections, scholarly articles, and literature discussing Islamic and Javanese cultural intersections. The findings reveal that Sekar Kedaton conveys core Islamic values such as honesty, justice, social responsibility, cleanliness as part of faith, patience, and empathy, all aligned with prophetic teachings. These values are presented in poetic form, making them accessible and memorable to diverse audiences. The syiir also reflects the cultural internalization of Islamic norms, particularly regarding family harmony, gender roles, and spiritual discipline. The study concludes that literary works like Sekar Kedaton can be strategically utilized in Islamic character education, offering culturally relevant content for both formal and informal learning settings. It recommends further comparative research on similar regional Islamic literary texts across Indonesia to uncover unique cultural da'wah patterns and enrich religious literary discourse. This research underscores the need to preserve and study traditional Islamic literature as both cultural heritage and a valuable educational resource.